Gambaran Histopatologi Organ Hati dan Ginjal Mencit Balb/c setelah Pemberian Krim Ekstrak Teh Hijau (Camellia sinensis L.) - Nining Sugihartini; M Alif Fajri (Universitas Airlangga, 2016)
Background:Development of green tea extract formulation with the addition of enhancers to increase the ability of epigallocatechin gallate to penetrate the skin layers has been done. Objective: The purpose of this study was to determine the effect of green tea extract cream that containing enhancers on the profile of kidney and liver histopathology. Methods: The study used 4 groups which each group was treated with different concentrations of extract (2,0%; 2,5%; 3,0%; 3,5%) and 1 control group. After 24 hours and 14 days of application of the cream, the mice were sacrificed. The liver and kidneys were weighed and made preparations histopathology. Results: The results of the study showed that there similar (p>0,05) of the weight ratio of the liver and kidneys of Balb/c mice after 24 hours and 14 days. As well the histopathological test indicated that there similar (p>0,05) of the liver and kidneys after 24 hours and 14 days of administration of green tea extract cream. Conclusions: The levels concentration of green tea extract in cream (2,0%; 2,5%; 3,0%; 3,5%) that contain enhancers do not affect the liver and kidney histopathological of Balb/c mice.